Penerapan Ide Kreatif pada Program Feature Televisi â€œNusantara Berceritaâ€ Edisi â€œBocah Sisih Kidulâ€ - Dewi, Agnesthia Maharani Sukma; Asiatun, Siti (Jurnal Ilmiah Multimedia dan Komunikasi, 2022)
The dropout rate in Indonesia is still quite high in several regions. One of them is in Gunungkidul Regency, Yogyakarta. The role of education outside of school is very important to help out-of-school children to continue to get an education. The Bosskid Halfway House is a social organization that provides educational and recreational opportunities for out-of-school children in Ngasem Hamlet, Gunungkidul Regency. The purpose of creating this production work is to implement a creative idea in the form of an audio-visual entitled â€œSisih Kidul Children's Halfway Houseâ€, which is outlined in a television feature program. The ideas and topics developed are suitable to be made into features because they provide interesting human interest values. The application of this creative idea was preceded by data collection in the form of descriptive and narrative with journalistic references to accuracy. Information is collected from various sources. Creative ideas are used from the concept-making stage to treatment by selecting the form of a feature program. In preparing the concept, creative ideas are applied so that the topics that have been determined can be packaged into an interesting television program. On-site observation was carried out to find interesting ideas that could be discussed in this feature work. From the data obtained, a discussion framework was developed, such as making sub-angles 1, 2 and 3. The sub-angles were delivered in 3 sequences which were packed with a duration of 17 minutes and were able to provide information quickly and uniquely to the audience.